GEOTHERMAL SYSTEM MODELING BASED ON THE GRAVITY DATA OF RENDINGAN-ULUBELU-WAYPANAS (RUW) GEOTHERMAL FIELD, LAMPUNG, INDONESIA - WIDYA PERMATASARI - NIM: 12314021, ANA
Indonesia is located along the archipelago that causes the emergence of volcanoes along the arc, thus Indonesia has a very high geothermal energy potential, such as the Rendingan-Ulubelu-Waypanas Geothermal Field in Tanggamus Regency, Lampung Province. Therefore, geophysical exploration is needed to obtain a better understanding of the geothermal activities and geological condition in the subsurface. One of the method that can be used is gravity method. The objective of this study is to determine the geothermal system model in Rendingan-Ulubelu-Waypanas (RUW) Geothermal Field, Lampung, Indonesia. The data used in this study is a Rendingan-Ulubelu-Waypanas Geothermal Field Complete Bouguer Anomaly Map of 2005. Then the analog map was converted into digital map for further data processing. Separation of regional and residual Bouguer anomalies has been performed using moving average and spectral filter methods, where the spectral analysis was conducted in 1D and 2D. The value of Bouguer background density used for 2.5D subsurface modeling is 2.67 g/cc. Residual Bouguer anomaly map shows an anomalous contrast around the volcano ring of the study area. From 2,5 D modeling result, the existence of high anomalies under Mount Waypanas in the southern part of research area was interpreted as a Tertiary Intrusion of Granite with a density contrast of +0.22 g/cc. While low anomalies in the northern part was interpreted as a Quaternary Intrusion of Diorite with a density contrast of -0.22 g/cc, which acts as the heat source of the system. The reservoir of the system is the Quaternary Young Volcanics exposed on the surface with averaged thickness of 1500 m. Fluid flow in this geothermal system is meteoric water from Mount Rendingan and Mount Tanggamus, flows to lower topographic area in the southern part, around Mount Waypanas, also creates an upflow mechanism in Mount Rendingan.